2019
DOI: 10.1002/adfm.201807692
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Fabrication of Gradient Nanoporous All‐Polysaccharide Films as Strong, Superfast, and Multiresponsive Actuators

Abstract: The design of smart hydrogel actuators fully constructed from natural polymers for assessing the biomedical applications is important but challenging. Herein, an extremely simple, green, and ultrafast strategy is presented for preparing robust gradient all-polysaccharide polyelectrolyte complex hydrogel actuators. Driven by diffusing of low molecular weight chitosan into high molecular weight sodium alginate solution, a nanoporous, ultrastrong, and gradient chitosan/sodium alginate complex hydrogel film with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 50 publications
2
78
0
Order By: Relevance
“…[ 12–14 ] The methods that are currently available for the fabrication of anisotropic structures include one‐step method, [ 15,16 ] layer‐by‐layer polymerization, [ 17–19 ] 3D printing, [ 20 ] photolithography, [ 21 ] and ion printing. [ 22,23 ] These actuators contain crosslinking structures, and chemical crosslinking usually fixes the anisotropic structures of soft actuators and stabilizes their actuation performance. However, the stable crosslinked structures restrict the reprocessing ability of the actuators.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–14 ] The methods that are currently available for the fabrication of anisotropic structures include one‐step method, [ 15,16 ] layer‐by‐layer polymerization, [ 17–19 ] 3D printing, [ 20 ] photolithography, [ 21 ] and ion printing. [ 22,23 ] These actuators contain crosslinking structures, and chemical crosslinking usually fixes the anisotropic structures of soft actuators and stabilizes their actuation performance. However, the stable crosslinked structures restrict the reprocessing ability of the actuators.…”
Section: Introductionmentioning
confidence: 99%
“…For smaller pore sizes, mainly polymeric membranes exhibiting graded porosity have been synthesized. This can be performed either postsynthetically by selective swelling approaches [31] or during synthesis by diffusion-controlled assembly processes [32]. Similar approaches can be transferred to fully inorganic materials, resulting in graded porous carbons after carbonization [27].…”
Section: Introductionmentioning
confidence: 99%
“…By manipulating the temporary shapes via shape memory behavior, various temporary anisotropic structures can be obtained via the bilayer hydrogel, thus producing diverse reversible shape deformation performances, which is expected to promote the development of intelligent polymeric materials. materials in the rising area of intelligent research, [6,7] have aroused increasing interest and shown promising applications in the fields of soft robotics, [8,9] biomedical engineering, [10][11][12] and biomimetic manufacturing. [13] In the past decade, simple bending, folding, and complex shape deformations have been achieved by inducing anisotropic structure such as gradient, [14,15] bilayer, [16,17] patterned, [18][19][20] or orient structure [21,22] in hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Nature is considered as the common source of inspiration in both designing and fabricating of intelligent materials. [ 1–5 ] Smart hydrogel actuators, one of the most anticipated materials in the rising area of intelligent research, [ 6,7 ] have aroused increasing interest and shown promising applications in the fields of soft robotics, [ 8,9 ] biomedical engineering, [ 10–12 ] and biomimetic manufacturing. [ 13 ] In the past decade, simple bending, folding, and complex shape deformations have been achieved by inducing anisotropic structure such as gradient, [ 14,15 ] bilayer, [ 16,17 ] patterned, [ 18–20 ] or orient structure [ 21,22 ] in hydrogel.…”
Section: Introductionmentioning
confidence: 99%